The training of school-doctors in France: ways of improvement, lessons to share. (30th September 2020) - Godeau, E; Chenel, S
Abstract: In France protection & prevention of students' health in schools is taken care of by school-doctors, in partnership. They follow a specific training for a year before becoming civil servants in the Ministry of Education. Around 1000 school-doctors are currently in post; 20-30 new school-doctors are trained each year. The training alternates academic sessions & supervised medical work in schools, under the responsibility of experienced mentors. Since 15 years, this training has been revised to improve its relevance in a Public health perspective, mainly by adding a strong health promotion component. The current organisation aims at (1) individualising the training, capitalising on the knowledge & competencies of trainees, leading to an individual scheme defined with the national coordinators (a school-doctor and a pedagogical engineer) between 8 & 16 weeks of academic sessions given at the French school of Public health; (2) articulating academic contents with pragmatic & professional skills; (3) integrating pedagogical innovations to maximise the development of the 10 competencies identified as core to school-doctors; (4) giving school-doctors a broad Public health perspective, with research and health promotion expertise, while fostering their specific and particular medical practice in the global context of schools. Each year improvements are implemented to answer the feed-back from trainees and professionals involved in the training. A closer articulation between local heads of school-doctors and the national level of their training has been fostered to improve coherence between academic & technical content while meeting ministerial requirements. The overall involvement & satisfaction of trainees are monitored. There is still space to improve the training of qualified school-doctors to promote the health of school-students in a Public heath perspective, in a time in France where health inequalities need to be better addressed and where the medical demography is critical. Key messages: In a time of lack of medical doctors, school-doctors are important public-health actors for children and adolescent, with a very crucial position at the articulation of the health and school systems. The training of school-doctors must meet the challenge to accommodate pedagogical requirements & changes in their practice due to vacant posts while fulfilling ministerial expectations.